Relationship of Dental Caries and Body Mass Index amongst School Children in Hail, Saudi Arabia: A Cross-Sectional Study - Alsweed, Ali (2023)
Objective: To determine caries prevalence and its association with body mass index in school children between 9-12 years of age in Hail, Saudi Arabia. Material and Methods: This descriptive cross-sectional study included 524 school children 9-12 years of age. These children were selected from 9 Public schools in Hail Province. Dental caries was recorded as per criteria established by the World Health Organization using assessment form for children 2013. Children were weighed using an electronic scale nearest to 0.1 kg with children attired in light clothing and wearing no shoes. The height was measured using a stadiometer to the nearest full centimeter with the children in a standing position. Body Mass Index (BMI) was determined using the formula BMI = kg/m2. Results: Caries prevalence in the population was 86%. The comparisons of mean DMFT between the groups demonstrate higher scores in the overweight group (mean=2.43) compared to normal weight (mean=1.85) and underweight children (mean=1.56) which is statistically significant (p=0.000). Bonferroni Post hoc test to compare the underweight and overweight group (p=0.000) and overweight and normal weight (p=0.000) were highly significant. Conclusion: A positive correlation of caries severity, namely DMFT, with BMI is established.